Management of primary hepatic malignancies during the COVID-19 pandemic: recommendations for risk mitigation from a multidisciplinary perspective. (August 2020) - Barry, Aisling; Apisarnthanarax, Smith; O'Kane, Grainne M; Sapisochin, Gonzalo; Beecroft, Robert; Salem, Riad; Yoon, Sang Min; Lim, Young-Suk; Bridgewater, John; Davidson, Brian; Scorsetti, Marta; Solbiati, Luigi; et al.
Summary: Around the world, recommendations for cancer treatment are being adapted in real time in response to the pandemic of COVID-19. We, as a multidisciplinary team, reviewed the standard management options, according to the Barcelona Clinic Liver Cancer classification system, for hepatocellular carcinoma. We propose treatment recommendations related to COVID-19 for the different stages of hepatocellular carcinoma (ie, 0, A, B, and C), specifically in relation to surgery, locoregional therapies, and systemic therapy. We suggest potential strategies to modify risk during the pandemic and aid multidisciplinary treatment decision making. We also review the multidisciplinary management of intrahepatic cholangiocarcinoma as a potentially curable and incurable diagnosis in the setting of COVID-19.